La formation visant la prise en charge globale des troubles musculo-squelettiques par l’entreprise : une étude exploratoire - Valérie Tremblay-Boudreault; Nicole Vézina; Denys Denis; Yannick Tousignant-Laflamme (Perspectives Interdisciplinaires sur le Travail et la Santé)
A training program was developed and implemented using a participatory ergonomics approach in order to improve prevention of MSD and related return to work management in a specific rubber plant. The results were observed under the angle of representation changes, workers’ participation to prevention and return to work and internal skill development. The main contribution of our intervention was to combine altogether prevention and return to work into the training program. Collaboration between the rubber plant’s actors and external resources seems to be essential in order to capitalize on proper MSD management in an industry with high level of constraints, where financial resources are limited and employees are at high risk of MSD.